(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2010)
The article deals with the level of production of confix morphemes with postpositive component –ок in the process of formation of animate nouns. It also investigates peculiarities of word-formative structure and semantics of noun confix derivatives with component ‑ок which are discovered in the monuments of the Ukrainian language. Sixteen confixes form these derivatives. In this connection the description of the facts is made in the order of decreasing of production of word-formative types.